Justiça, psiquiatria e outras drogas: instituições fissuradas pelo manicômio judiciário - Assis, Daniel Adolpho Daltin (2019)
In Brazil of the last century, the history of madness has in jail an important social alibi and propeller of periculosistas discourses. In this century, the driving force of gear is intensified as drug use presents itself as a fundamental component to include the judicial asylum in the drug war agenda. In the present research, we have exposed the judicial context in which the consumption of psychoactive substances has repercussions on the judicial determination of compliance with security measures at the Institute of Forensic Psychiatry of Paraiba. Our objective was to understand how the use of drugs becomes an element of discursive formations that, in the name of control over dangerousness, urge judicial authorities to subject the subject to compulsory criminal-psychiatric treatment. We selected the period from 2002 to 2017, in the foreground, we obtained quantitative results on the judicial-manicomial reality in the state, based on data collected from criminal cases of 256 people who went through the asylum. Through filters within this universe, in the second moment, we focus on 12 processes that have mobilized us to analyze the discourses around the triple interface drug use / prison / psychiatry, which result in the determination of the security measure of hospitalization. We aim to understand the discourses that guide and underlie the relations of power, both individualizing and totalizing, in the construction of the institutional security route for which the debate about drug use competes. Despite the fact that, under the current drug law, such behavior no longer leads to imprisonment - a reality to which are added the effects of the three-year-old Brazilian psychiatric reform, which has not turned itself to crazy offenders - escape to the mental asylum seems inevitable for history and seductive to the judicial authorities. Through six categories called limit situations, accompanied by guiding questions, we analyzed discourses that orbited around the following themes: criminal detraction, expert reports, alcohol and other drugs, technical defense, divergence between law and psychiatry, family responsibility. There were more contradictions than solutions. Paths have been opened that have shown us that the institutional itinerary of security to which the person in question is subjected, dangerously, plays with time, word and subject in Foucauldian speech of the ubuesque. From this labyrinth we proposed strategic exits that go beyond the theoretical reflections, the struggles for the guarantee of human rights of this doubly assuaged population